2013
DOI: 10.1017/s1461145713000060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic social defeat stress on behaviour, endoplasmic reticulum proteins and choline acetyltransferase in adolescent mice

Abstract: The present study investigated the effects of social defeat stress on the behaviours and expressions of 78-kDa glucose-regulated protein (Grp78), CCAAT/enhancer-binding protein (C/EBP) homologous protein (CHOP) and choline acetyltransferase (Chat) in the brains of adolescent mice. Adolescent male C57BL/6J mice were divided into two groups (susceptible and unsusceptible) after 10 d social defeat stress. In expt 1, behavioural tests were conducted and brains were processed for Western blotting on day 21 after st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 49 publications
8
49
0
1
Order By: Relevance
“…Furthermore, when assessing sensitivity to a subsequent helplessness-related stressor, namely the forced swim test, we found that defeated adolescent mice displayed increased sensitivity to despair measures, as inferred from decreased time to adopt a posture of immobility and a total increased time spent immobile, when compared to controls (Figure 2). This depression-like behavioral phenotype resembles that of early-adult (~PD56) c57BL/6 male mice exposed to a similar defeat stress regimen (Huang et al, 2013), yet here, we extend these findings to mid-adolescence (PD45), the developmental stage when the first incidence of depression is most commonly reported (Burke et al, 1990). Because social avoidance and increased helplessness behaviors are considered symptoms of numerous psychiatric illnesses in addition to major depression (APA, 2000; Berton et al, 2006), we assessed whether adolescent social defeat would influence sucrose preference in a two-bottle choice test as a complementary measure of depression-like behavior.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, when assessing sensitivity to a subsequent helplessness-related stressor, namely the forced swim test, we found that defeated adolescent mice displayed increased sensitivity to despair measures, as inferred from decreased time to adopt a posture of immobility and a total increased time spent immobile, when compared to controls (Figure 2). This depression-like behavioral phenotype resembles that of early-adult (~PD56) c57BL/6 male mice exposed to a similar defeat stress regimen (Huang et al, 2013), yet here, we extend these findings to mid-adolescence (PD45), the developmental stage when the first incidence of depression is most commonly reported (Burke et al, 1990). Because social avoidance and increased helplessness behaviors are considered symptoms of numerous psychiatric illnesses in addition to major depression (APA, 2000; Berton et al, 2006), we assessed whether adolescent social defeat would influence sucrose preference in a two-bottle choice test as a complementary measure of depression-like behavior.…”
Section: Discussionsupporting
confidence: 59%
“…However, social defeat also produces a small subgroup of animals that do not develop social avoidance, described as resilient mice (Krishnan et al, 2007). While the present results mirror those of adult rodents, future studies will be needed in order to examine if the resilient-like behavioral phenotype is evident in adolescent male c57BL/6 mice, as it is reported in early-(Huang et al, 2013) and mid-adulthood (Krishnan et al, 2007). Also, a limitation of the present study is that we did not assess the effects of social defeat stress in adolescent female subjects, thus hindering the interpretability of our results to the clinical setting, where twice as many girls (versus boys) are diagnosed with major depression (Hankin et al, 1998).…”
Section: Discussionsupporting
confidence: 59%
“…Thus, SDS+SIS leads to profound psychoemotional changes in adolescents, which affect their social and individual behaviors. This conclusion is also supported by studies demonstrating development of increased anxiety after social isolation stress [4] and under social instability stress [30], [33] and depressive-like behavior under SDS [34] or chronic mixed-modality stressors (isolation, restraint and SDS) [12] in adolescent male and female rats.…”
Section: Discussionsupporting
confidence: 58%
“…While the origin of hippocampal cholinergic neurons is relatively unclear, it is known that certain long axons expressing ChAT terminates in the hippocampus, and are involved in the modulation of hippocampal synaptic plasticity (Melander et al, 1985; Kaufer et al, 1998; Huang et al, 2013). Like the observations in other presynaptic excitatory system (VGLUT 2), hippocampal and cortical ChAT expression decreased significantly in naïve stressed rats, and was reversed after PET (increased).…”
Section: Discussionmentioning
confidence: 99%